SERO-SURVEILLANCE OF “PESTE DES PETITS RUMINANTS” PPR IN MONGOLIA AND DEVELOPMENT OF RECOMMENDATION - Ts., Undrakhbayar; E., Uuganbayar; R., Odbileg (Mongolian Journal of Agricultural Sciences, 2017)
PPR (Peste des Petits Ruminants) is a transboundary disease, listed in the OIE Terrestrial Animal Health Code, which Mongolia and other countries are obligated to report the disease to the OIE according to the criteria [1]. Purpose of this study is to conduct sero-epidemiological survey for detection of PPR antibody in livestock and susceptible animals from aimag, soums near border area because 244 outbreaks have been recorded [2] in China mainland since September, 2013. A total of 1950 goat and sheep serum samples from 52 soums of 15 aimags have been examined by “ID VET” Competitive ELISA kit for antibody detection. Result showed that PPR virus antibodies have been found in 12 samples from 1550 sheep, and 4 samples from 400 goat samples which have been examined. The same result has been shown after the re-testing the positive samples by ELISA with the serum titration of 1:4 and 1:8. PPR Global strategy for prevention, control and eradication of PPR by 2030, has been developed by OIE and FAO [14]. PPR recommendation has been developed in accordance with the Global strategy and sero-surveillance conducted in Mongolia.